INKLUSIVISME WANITA BERCADAR DI ERA KONTEMPORER: Studi Kasus Komunitas Cadar Garis Lucu - Harifuddin, Abd Azis (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
This study discusses the religious dynamics of veiled Muslim women through the case of the online community “Cadar Garis Lucu” (CGL). Using a qualitative case study approach, data were collected through observation, interviews, and digital documentation. The findings reveal that CGL constructs an inclusive and fluid Islamic identity, diverging from the typical conservative stereotype. Through humor, popular culture, and social media engagement, the community reshapes a more open and adaptive religious narrative. This research contributes to new perspective on the transformation of Islamics symbols and identity among contemporary Muslim women.